The Family Upstairs - Jewell, Lisa (New York, NY : Pocket Books, an imprint of Simon & Schuster, Inc, 2023)
Soon after her twenty-fifth birthday, Libby Jones returns home from work to find the letter shes been waiting for her entire life. She rips it open with one driving thought : I am finally going to know who I am. She soon learns not only the identity of her birth parents, but also that she is the sole inheritor of their abandoned mansion on the banks of the Thames in Londons fashionable Chelsea neighborhood, worth millions. Everything in Libbys life is about to change. But what she cant possibly know is that others have been waiting for this day as well--and she is on a collision course to meet them. Twenty-five years ago, police were called to 16 Cheyne Walk with reports of a baby crying. When they arrived, they found a healthy ten-month-old happily cooing in her crib in the bedroom. Downstairs in the kitchen lay three dead bodies, all dressed in black, next to a hastily scrawled note. And the four other children reported to live at Cheyne Walk were gone. In The Family Upstairs, the master of "bone- chilling suspense" (People) brings us the cant-look-away story of three entangled families living in a house with the darkest of secrets."--
Keywords: Family secrets -- Fiction; Orphans -- Fiction; Inheritance and succession -- Fiction; Mansions -- England; London; Fiction; Cold cases (Criminal investigation) -- Fiction; Chelsea (London, England) -- Fiction; England -- Fiction; Thrillers (Fiction); Psychological fiction